Evaluation of Performance Quality of Workers in Medical Laboratories within the Health Sector under the Corona Pandemic in Al-Muthana Governorate/Iraq - Ali Harb, Noor; Kadhim Jasim , Alaa (University of Thi-Qar Journal of Science, 2023)
Laboratory performance is a relative concept, but it is crucial in the whole testing process, as are quality and safety.  The study aimed to assess the quality of performance of workers in medical laboratories within the health sector during the Corona pandemic.  Materials and Methods: This cross-sectional study was conducted at 3 hospitals, 19 PHCCs distributed in 5 sectors, and 1 Public Health Laboratory randomly selected ( using a   Multistage random sampling method) in Muthanna governorate.  The period of study starts on 1 December 2021 – 31 March 2021.Results: The study found that 77.0% of the participants had a moderate assessment score, followed by 20.4%having a good assessment score. At the same time, the lowest percentage (2.6%) of the employees have a poorassessment score.